Handbook of Terminology Management : Volume 1: Basic Aspects of Terminology Management. - Wright, Sue Ellen (John Benjamins Pub. Co., 1997)
The Handbook of Terminology Management is a unique work designed to meet the practical needs of terminologists, translators, lexicographers, subject specialists (e.g., engineers, medical professionals, etc.), standardizers and others who have to solve terminological problems in their daily work. In more than 900 pages, the Handbook brings together contributions from approximately 50 expert authorities in the field. The Handbook covers a broad range of topics integrated from an international perspective and treats such fundamental issues as: practical methods of terminology management; creation.